Valoración del estado nutricional y detección del riesgo de caída de los adultos mayores de acuden a los centros gerontológicos de la ciudad de Loja. - Bravo Guamán, Darwin Vinicio (2017)
The world population is aging and as people age they are increasingly at risk of malnutrition, at risk of falling, and suffering from fall injuries, due to intrinsic and extrinsic factors associated with old age, which increases morbidity and mortality and decreases functionality. The objective of this study was to determine the nutritional status and risk of falls in the elderly who go to the gerontological centers of the city of Loja to design a nutritional support and fall prevention instruction; this was a quantitative, descriptive and cross-sectional type, realized to 103 elderly adults; for data collection, the Mini Nutritional Assessment (MNA) was used to determine the nutritional status and Tinetti's test for the determination of fall risk. It was evidenced that of the 103 older adults, 36.9% had a risk of malnutrition, which was higher in males (43.5%) and in the elderly, aged 85 years and older (42.9%). 8.7% presented malnutrition, being equally representative in the male sex (15.2%) and in the elderly between 75-84 years of age (16.7%). Regarding the detection of the risk of falls, it was determined that 36.9% presented a high risk of falls, predominantly male (45.7%) and elderly (48.6%). It was also observed that in women (29.8%), the most representative fall-related alteration was associated with balance disorder, whereas in men (34.8%) it was the gait disorder. It is concluded that older males and those in the age group of 85 years and older are the most vulnerable to falls and malnutrition. As age increases, the risk of falls is also increased as a result of aging and due to the disorders of the systems that allow to maintain the balance and the march. Key words: Older adult, risk of falls, malnutrición.